Rotationally symmetrical spoof-plasmon antenna for polarization-independent radiation enhancement - Zheng, Xin (2023)
Plasmon antennas allow subwavelength confinement and enhancement of electromagnetic fields at the “hotspot” where the radiation efficiency of emitters can be substantially enhanced. Such enhancement, however, is often polarization dependent. Consequently, the radiation behaviors (e.g., radiation pattern and polarization states) of the emitter placed at the hotspot are also modified significantly. Enhancing the radiation efficiency without altering the original radiation pattern and polarization state of the emitter is highly desired for many sought-after applications involving chiral emitters but remains a challenging task, especially at low frequencies. To this end, spoof-plasmon antennas with fourfold and sixfold rotational symmetries are designed and realized experimentally. These plasmon antennas support polarizationindependent localized plasmon resonances, which can significantly enhance the local density of photonic states at the structural center without changing the polarization state of the emitter. As a typical example, the structure with sixfold rotational symmetry is coupled with a half-wave dipole antenna. The measurement results show that the far-field radiation pattern of the dipole antenna is maintained with the radiation efficiency enhanced by more than 2 orders of magnitude, irrespective of the dipole orientation.